Koorero tuku iho : waahine Maaori : voices from the embers of Rangiaowhia : a thesis presented in partial fulfillment of the requirements for the degree of Master in Adult Education at College of Education, Massey University, Palmerston North - Coromandel-Wander, Hazel (Massey University, 2013)
When will the mokopuna stop inheriting the hara of Rangiaowhia? Koorero tuku iho, is based on oral traditions praxis of my kuia as ‘handed down’ by three generations of her whaanau, for her mokopuna. Her eyewitness account of the massacre at Rangiaowhia February 1864, ‘talks back’ to the oppressive power systems that brand the indigenous as guilty. “History can frequently dismiss whole groups of people as lost causes, or as irrelevant. Entire sections of society, usually the poor, the minorities, and the politically powerless are thereby obliterated from memory (Binney & Chaplin 1990:3)”. Ultimately, it is only through re-claiming, re-defining and re-storing of the principle of tino rangatiratanga that the hara can be lifted from Ngaati Apakura mokopuna. However, it is through the discursive practice of koorero tuku iho by and from Ngaati Apakura voices that the burden and prejudice can be brought out of obscurity into open dialogue with the Crown. This study is an indigenous history lesson on core taonga tuku iho praxis as handed down from grandmother to mokopuna in daily actions that seek to restore the balance. This is the legacy of the waahine Maaori intergenerational indigenous literacy’s that seek for indigenous justice and freedom from oppression.
Keywords: Ngāti Apakura; Maori women; Oral tradition; Ethnic identity; History; Wāhine Māori; Waikato; New Zealand; History; Kōrero nehe